Financial feasibility analysis of the fortifer business model in the Cape Coast Metropolis in Ghana - Aboah, J.; Gebrezgabher, Solomie A.; Meuwissen, M.P.M. (2014)
This study seeks to analyse the financial feasibility of upscaling the fortifer business model in Ghana. Data originate from the pilot project in Accra, extended with expert elicitation. The NPV and IRR were used as decision criteria for Public Private Partnership (PPP) and Private Scenarios. The Spearman rank correlation coefficient was used to identify input parameters which had most impact on NPV. Economic and simulation results reveal higher probability of financial feasibility in the PPP Scenario. Outcomes are useful for policy makers to jointly steer urban waste management and farmers’ needs in the area of sustainable soil management.